A theory and outcome evaluation of the Allan Gray Orbis Foundation Association programme - Modubi, Ngoakwana Nkakga (School of Management Studies, 2026)
Introduction: This dissertation presents the outcome and theory evaluation of the Allan Gray Orbis Foundation (AGOF) Association programme. The Association programme is a lifelong support network for fellowship programme alumni aimed at fostering responsible entrepreneurship by providing continuous development opportunities through industry experiences, workshops, seminars, business accelerators and access to funding. Its long-term goal is to cultivate entrepreneurial competence by equipping fellows with resources to start and grow their ventures and by supporting those in employment to foster an entrepreneurial mindset within the workplace. The evaluation addressed key questions to assess the programme theory and the outcomes. Methodology: The theory evaluation systematically assessed the validity and effectiveness of the programme's underlying theory of change. Key components included evaluating the causal mechanisms within the theory of change to determine its plausibility, as supported by the literature. Additionally, seven subject matter experts, including entrepreneurial professionals, were interviewed during the evaluation process. These experts contributed valuable insights into the programme's theory of change, leveraging specialised knowledge and experience in entrepreneurship to validate the assumptions and logic underpinning the theory of change. Furthermore, a qualitative approach was employed using the Success Case Method (SCM) for the outcome evaluation. This method identified whether the intervention was effective and explored opportunities for improvement. Qualitative data were collected from eleven success cases and five non-success participants, providing comprehensive insights into the programme's impact. The qualitative data for the subject matter expert interviews was analysed using content analysis to interpret findings and reduction analysis for the success and non- success case semi-structured interviews. Ethical considerations were prioritised throughout the process, ensuring participants' informed consent, anonymity and confidentiality while addressing potential harm. Findings: The programme theory of change was plausible. Access to capital was identified as a critical component for the programme's success. Experts emphasised that while financial resources are essential, they must be paired with a supportive network to maximise impact. In addition, the theory evaluation highlighted the importance of participation in entrepreneurship mindset development increased the likelihood of the establishment of socially responsible, high-impact enterprises. Research suggests that these activities can equip fellows with essential skills and knowledge while fostering a commitment to ethical business practices and social responsibility. The theory evaluation also identified the importance of a structured entrepreneurial programme pipeline to support the continuous development of fellows into socially responsible, high- impact entrepreneurs. Results from the outcome evaluation, utilising the SCM, found that the programme beneficiaries successfully foster an entrepreneurial mindset, equipping the fellows with problem-solving and resilience skills, which they apply in both business ventures and corporate environments. Most fellows reported that the programme assisted them in navigating workplace challenges, driving innovation, and influencing decision-making processes. Furthermore, the programme facilitates community engagement and leadership development, evident by the fellows' contributions through mentorship, volunteering, event organisation, and financial support. These activities strengthened the network among fellows, fostering a culture of knowledge-sharing and social responsibility. Despite this, engagement levels were inconsistent, with some fellows highlighting communication gaps and unclear programme expectations as barriers to active participation. Moreover, while E² was a valuable funding resource, some beneficiaries noted that the slow and rigid application process hindered its effectiveness, with some fellows struggling to secure capital when needed. E² was, however, acknowledged for preparing fellows to pitch to venture capitalists and providing patient capital for business growth. As requested by the client, an evaluation of the AGOF pipeline was conducted to identify its strengths and weaknesses. Findings suggested that while the long-term support structure from the Scholarship programme to the Fellowship programme to the Association programme effectively nurtures entrepreneurial talent, gaps in transitioning Scholarship recipients into the Fellowship were noted. Conclusion: The Association programme has made a meaningful impact on its beneficiaries, contributing to their growth and success. The integration of access to capital, targeted development activities, and a comprehensive programme pipeline is crucial for nurturing successful entrepreneurs through the Association programme. The insights gained from this evaluation provide a solid foundation for future research and practical recommendations to enhance the programme's effectiveness.